Changes in Plasma Sex Hormone Levels in Women with Severe Concomitant Injury - K. N Yezhova; A. V. Volkov; V. V. Moroz (Общая реаниматология)
Objective: to perform a complex study of the plasma levels of 11 sex hormones and their functional values in women with severe concomitant injury (SCI). Subjects and methods. The study enrolled 16 women aged 18—45 years who had SCI. Admission APACHE II scores were 18.9±1.3. According to the outcome of a posttraumatic period, all the patients were divided into 2 groups: A) survivors; B) deceased subjects. The normal values were used to comparatively analyze the concentrations of reproductive hormones. The time course of changes in hormone concentration was studied on postoperative days 1, 3, and 7. The hormone profile was examined by BSL test kits (USA) on a STAT Fax 2100 enzyme immunoanalyzer (Awareness Technology Inc., USA). The content of prolactin, luteinizing hormone, follicle-stimulating hormone, progesterone, 17-hydroxyprogesterone, dehydroepiandrosterone sulfate (DHEA-S), androstendione (A), testosterone (T), dihydrotestosterone, estrone, and estradiol (E) were measured. Results. The complex study of changes in the profile of 11 plasma sex hormones was first conducted in women in the posttraumat-ic period. Moreover, the typical plasma hormonal changes were elevated prolactin levels, a decrease in the concentrations of gonadotropins, and increases in some androgens, A, T, and E. The deceased women showed lower concentrations of DHEA-S and T. Analysis revealed an inverse correlation between the plasma concentration of DHEA-S and the injury severity. This change seems to suggest that an adrenal adaptation reaction is exhausted. The changes revealed in hormonal levels are of significance in understanding the pathogenesis of SCT. This may serve as a basis for the development of new therapy modalities using reproductive hormones in the postresuscitative period. Key words: severe concomitant injury, sex hormones, prolactin, luteinizing hormone, follicle-stimulating hormone, progesterone, 17-hydroxyprogesterone, androgens, estrogens.